Hyaluronic acid induced foreign body reaction mimicking neoplastic parotid cytology. Issue 9 (2nd May 2019) - Davis, Adam; Basu, Devraj; Suyash, Mohan; Jalaly, Jalal B.
Abstract: Masses near the angle of the mandible containing extracellular matrix or mucin on cytology raise concern for various benign and malignant parotid gland neoplasms. Here a 76‐year‐old female with a history of cosmetic hyaluronic acid (HA) filler injections presented with a painless 6 mm left sided facial mass. Injection of hyaluronidase into the mass had failed to cause regression, raising concern for a neoplastic process. Fine‐needle aspiration (FNA) showed amorphous, mucinous/extracellular matrix‐like material in a background of numerous histiocytes and occasional multinucleated giant cells, consistent with a foreign body giant cell reaction to HA. This uncommon reaction to HA filler creates previously unrecognized diagnostic pitfalls because of its resemblance on FNA to the extracellular matrix or mucin found in many salivary neoplasms.